Trade policy: 'Institutional' vs. 'economic' factors - Stefan Lutz (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
The ongoing discussion of U.S.-Japanese trade relations suggests that national differences such as in the institutional environment may be relevant for assessing international trade policies. However, economic trade theory often assumes countries to be organized around common notions of complete markets. This paper compares two alternative modes of trade policy analysis by juxtaposing the “economic” view inherent in Gene Grossman's work on “Japan's Innovation and Trade” with the “political” view of “Japanese-American Relations” expressed by Chalmers Johnson. A synthesis is attempted with the help of some remarks on “New Trade Theory's Implications for Policy Analysis” by John Pomery.
Keywords: A12; B41; F10; 330; trade theory; policy; institutional factors; Außenwirtschaftspolitik; Internationale Wirtschaftsbeziehungen; Komparativer Kostenvorteil; Institutionalismus; Neue Außenhandelsthe